Environmental Stress Created by Chemical Pollution in the Marmara Sea (Turkey) - BURAK, SELMIN; UNLU, SELMA; GAZIOGLU, CEM (Asian Journal of Chemistry, 2010)
The ecological consequences of chemical pollution experienced as evidence of significant environmental stress in the Marmara sea which is a semi-enclosed internal basin with a stratified structure. The stratification is due to the Mediterranean sea originated lower layer current and Black sea originated upper layer current that hinders the water circulation. Rapid urbanization on the coastal zone of the Marmara sea has attracted population since the 1970's. This has been one of the main reasons for the pollution that has affected primarily the estuaries and bays of the Marmara sea and has ultimately spread along the shoreline and continental shelf that constitutes 50 % of its total area. The Marmara sea coastal zone is at risk of severe industrial and domestic pollution where hot-spots comprise Izmit, Gemlik, Bandirma bays and Greater Istanbul Metropolitan area. Chemical pollution accumulated in the bays, in particular, has created significant ecological damage resulting in the decrease or extinction of marine species. In this paper, the oceanographic features of the receiving media, the sources of industrial and domestic pollution based on field data and monitoring are presented. Previous studies and the present one carried out so far reveal that a good understanding of the oceanographic and ecological processes is essential for the Marmara sea as a whole. In the light of the findings, the means and tools for an integrated wastewater management plan in the Marmara region are discussed.